INDIA-MIDDLE EAST-EUROPE CORRIDOR (IMEC): RHETORIC, REALITIES AND IMPLICATIONS FOR PAKISTAN (Margalla Papers, 2024)
This research article explores the India-Middle East-Europe Corridor (IMEC) to ascertain whether it is a myth or a reality. It also examines its transparency, timeliness, and primary objectives. Against the backdrop of instability in the Middle East, mainly arising from the ongoing Gaza situation, the study assesses the regional and global implications of the IMEC, considering arguments both in favour and against the initiative. Nevertheless, the problem has a similar impact on all such ventures as China’s Belt and Road Initiative (BRI) since the successful realisation is contingent upon the stable and enabling regional environment. This exploration suffers from the challenge of access to authentic sources. Given the contemporary nature of the subject matter, this study will primarily rely on secondary literature. Employing an Intergovernmentalism theoretical approach, this research delves into the dynamics of IMEC, discussing its intended objectives and challenges. The central argument contends that a meticulous analysis of the corridor's cause and effect on Pakistan's economic and geostrategic interests is imperative. The IMEC initiative exhibits the potential of a relatively cheap system, enhancing contemporary transportation infrastructure. However, the study asserts that the IMEC presents an obvious threat to the China-Pakistan Economic Corridor (CPEC) and the BRI, potentially compromising Pakistan's economic and strategic interests. The paper adopts a nuanced perspective, emphasising that IMEC and BRI contrast in strategic planning and development approaches. Should the IMEC materialise according to its envisaged plan, it will yield substantial diplomatic, strategic, and economic benefits for India. The article concludes by underscoring the challenges faced by IMEC, including coordination complexities, financial constraints for some participating nations, and potential geopolitical tensions affecting corridor operations. Bibliography EntryKhan, Raza Ali. 2024. "India-Middle East-Europe Corridor (IMEC): Rhetoric, Realities and Implications for Pakistan." Margalla Papers 28 (1): 75-92.